2020
DOI: 10.1108/cpoib-12-2019-0106
|View full text |Cite
|
Sign up to set email alerts
|

MNCs’ open international strategy–local dynamics: transfer of German “vocational education and training” to emerging economies

Abstract: Purpose This paper aims to examine multinational companies’ (MNCs) international transfer strategies of German vocational education and training (VET) and examines the dynamics in the subsidiaries. Design/methodology/approach Methodologically, the study is based on expert interviews conducted in German headquarters. To complete the picture, the study also includes insights from expert interviews in subsidiaries in Mexico, India and China. Findings There is a mix of country-of-origin and geocentric strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…The findings have also revealed the strong influences of local conditions in this regard. For example, Wiemann and Pilz (2020) explored qualification strategies used by German multinational companies in India, Mexico, and China using both comparative VET research and applying the international human resource management perspective (see also Pilz and Wiemann 2020;Vogelsang and Pilz 2020;Fuchs 2020). They found that even in German companies in foreign countries, the dual training commonly used in Germany is only offered for a few specialists in some larger companies.…”
Section: Transfer In Comparative Vet Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings have also revealed the strong influences of local conditions in this regard. For example, Wiemann and Pilz (2020) explored qualification strategies used by German multinational companies in India, Mexico, and China using both comparative VET research and applying the international human resource management perspective (see also Pilz and Wiemann 2020;Vogelsang and Pilz 2020;Fuchs 2020). They found that even in German companies in foreign countries, the dual training commonly used in Germany is only offered for a few specialists in some larger companies.…”
Section: Transfer In Comparative Vet Researchmentioning
confidence: 99%
“…Edwards, Colling, and Ferner 2007). The following discussion explores the transfer of strategies from one country to another, but it is more concerned with knowledge transfer and knowledge diffusion than with policy transfer (Wiemann 2019;Wiemann, Ventura, and Fuchs 2019;Fuchs 2020). Dickmann and Müller-Camen (2006) introduced the term 'knowledge networking' in this context.…”
Section: Transfer In Human Resource Management and Economic Geographymentioning
confidence: 99%
See 1 more Smart Citation
“…This is known as (neo-)Taylorist work organization. However, there are some opposing tendencies, for example in the metropolitan regions of the emerging economies, especially in the metalworking and chemical industries (Fuchs, 2014(Fuchs, , 2020Wiemann & Fuchs, 2018). These insights on (limited) vocational skills in subsidiaries are relevant for VET-related and geographic research, since such skills can contribute to personality development and workers' agency, as well as to local development (Asheim & Coenen, 2007;Boschma et al, 2013;Phelps et al, 2018).…”
Section: Theoretical Concept: Mncs' International Subsidiaries and Local Skillsmentioning
confidence: 99%
“…Research on countries of the Global South shows that there are ‘varieties’ of regional actor networks. A comparison between India, Mexico and China illustrates that particularly smaller multinational companies need cooperation partners on a local level to provide training but that these partners must meet different local conditions (Fuchs, 2020; Pilz & Wiemann, 2020). Local conditions can vary, which has an influence on training concepts and thus also on cooperation between actors (Vogelsang & Pilz, 2020).…”
Section: Conceptual Approach: Regional Actor Networkmentioning
confidence: 99%